Measuring dairy herd heat detection: the use of inter-service intervals - Remnant, John (2019)
Good oestrus detection is essential for efficient reproductive performance in dairy herds using artificial insemination. Veterinary surgeons and farmers use a variety of tools to measure and monitor oestrus detection, including the analysis of inter-service intervals (ISIs), which rely on an estimation of the normal oestrous cycle length. The normal oestrous cycle length of the cow is also important more broadly when managing and monitoring dairy herd fertility. Whilst the normal inter-ovulatory interval is typically considered to be 21 days, some studies have found alternative intervals to be more prevalent. The aim of this project was to evaluate and develop the use of inter-service interval analysis for the assessment of oestrus detection in dairy herds.